Prosocial behavior associated with trait mindfulness, psychological capital and moral identity among medical students: a moderated mediation model - Liu, Nana; Cao, Yanjun; Xu, Haibo (Frontiers in Psychology, 2024)
Purpose As future doctors, medical students’ prosocial behaviors may affect the relationship between doctors and patients. This study aims to explore the effects of trait mindfulness on prosocial behaviors, as well as the mediating role of psychological capital and the moderating role of moral identity among medical students. Methods A cross-sectional survey was conducted between July and October 2023 across four medical colleges in China, using cluster random sampling. The questionnaire included general demographic information, the Prosocial Tendencies Measurement Scale, the Five-Facet Mindfulness Questionnaire, the Psychological Capital Questionnaire, and the Moral Identity Scale. The SPSS 25.0 and PROCESS v3.4 macro were used for descriptive statistics, correlation analysis, and mediation and moderation analyses. Results A total of 2,285 samples were included. The analyses showed that prosocial behavior was positively correlated with trait mindfulness, psychological capital, and moral identity (r = 0.293, 0.444, and 0.528, p < 0.01); trait mindfulness predicts prosocial behavior (β = 0.292, 95% CI [0.253, 0.332]); and psychological capital played a partial mediation role between trait mindfulness and prosocial behaviors (β = 0.413, 95% CI [0.368, 0.459]). Furthermore, moral identity played the moderating roles between trait mindfulness and prosocial behavior (β = 0.049, 95% CI [0.011, 0.087]) and between PsyCap and prosocial behavior (β = 0.062, 95% CI [0.032, 0.092]). Conclusion Trait mindfulness, psychological capital, and moral identity are conducive to the development of medical students’ prosocial behavior. These findings provide evidence for the cultivation of prosocial behaviors and for the development of mental health courses, which should be tailored to medical students.